2017
DOI: 10.3389/fpls.2017.00372
|View full text |Cite
|
Sign up to set email alerts
|

In silico MCMV Silencing Concludes Potential Host-Derived miRNAs in Maize

Abstract: Maize Chlorotic Mottle Virus (MCMV) is a deleterious pathogen which causes Maize Lethal Necrosis Disease (MLND) that results in substantial yield loss of Maize crop worldwide. The positive-sense RNA genome of MCMV (4.4 kb) encodes six proteins: P32 (32 kDa protein), RNA dependent RNA polymerases (P50 and P111), P31 (31 kDa protein), P7 (7 kDa protein), coat protein (25 kDa). P31, P7 and coat protein are encoded from sgRNA1, located at the 3′end of the genome and sgRNA2 is located at the extremity of the 3′geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Since WSS larvae eat plant tissues for survival, it is very likely that plant miRNAs are taken inside of the insect body within their dietary consumptions. Several studies have provided evidence of trans -kingdom transfer of sRNAs from plant to other species which are in close contact; plant to virion ( Iqbal et al, 2017 ), plant to nematodes ( Tian et al, 2016 ), and plant to animal during feeding ( Zhang et al, 2012 ). Wheat miRNAs might also act as the regulators of insect metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since WSS larvae eat plant tissues for survival, it is very likely that plant miRNAs are taken inside of the insect body within their dietary consumptions. Several studies have provided evidence of trans -kingdom transfer of sRNAs from plant to other species which are in close contact; plant to virion ( Iqbal et al, 2017 ), plant to nematodes ( Tian et al, 2016 ), and plant to animal during feeding ( Zhang et al, 2012 ). Wheat miRNAs might also act as the regulators of insect metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs from one species may function at interspecies level, targeting genes or genomes of organisms which they have physical contact. Very recently, independent studies have been reported several examples of trans -kingdom delivery of sRNAs from; plant to virion ( Iqbal et al, 2017 ), oomycetes to plant ( Jia et al, 2017 ), plant to nematodes ( Tian et al, 2016 ). Similar to what these studies suggested, miRNAs might also be effective in regulating insect–host interactions at WSS larval stages once larva gets into the stem of the host plant.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies have been published previously using multiple computational algorithms to identify a best fit miRNA for a desirable target to understand plant-virus interaction. First time, genome-wide identification and comprehensive analysis was carried out to predict maize (Zea-mays)-encoded miRNA targets against maize chlorotic mottle virus (MCMV) (Iqbal et al, 2017). We have adopted the same novel computational strategy to predict the sugarcane-encode miRNA targets in the SCBGAV genome to combat badnaviruses in sugarcane.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are now being prioritized in the molecular research for their diverse cellular applications from the post-transcriptional regulation to gene expression [84,85]. Although miRNAs have been extensively studied for several years in many plant species [86,87,88], but no systematic study has been performed on the C. capsularis. The present study was carried out to identify the putative conserved microRNA candidates from the genome of C. capsularis by employing different screening process.…”
Section: Discussionmentioning
confidence: 99%